Social Media and English Learning: The Study of Students’ Vocabulary Enhancement at SMK Negeri 3 Padang - Yunisa, Nelsi; Oktavia, Witri (Journal of English Language Teaching, 2024)
Social media can affect people’s life in every aspect by several ways according to the user’s intention and frequency while using it. People could learn, play, and discuss with each other through social media. So, there are not only adult people who are addicted to use social media, but also the students. It could have a relation with learning English, especially learning vocabulary. This study aims to find out whether the students use social media sites to learn in order to improve or increase their English vocabulary. Furthermore, this study objectified among EFL students especially SMK Negeri 3 Padang in Indonesia. The population and the sample will be taken for this study is the students in grade 11 which totally 303 students averagely. In this study, the researcher used questionnaires as a tool. Thus, the result of this study shows that the respondents, students of SMK Negeri 3 Padang, utilize social media for enhancing their English vocabulary knowledge and produce a positive category on perceptions in using social media for learning vocabulary which means that they consider that social media can help them in terms of learning. Although, there are still several challenges faced by the students when learning vocabulary via social media.